The Long-Term Effects of Non-Pharmacological Interventions on Diabetes and Chronic Complication Outcomes in Patients With Hyperglycemia: A Systematic Review and Meta-Analysis - Zhou, Rongrong; Cui, Yashan; Zhang, Yuehong; De, Jin; An, Xuedong; Duan, Yingying; Zhang, Yuqing; Kang, Xiaomin; Lian, Fengmei (Frontiers in Endocrinology, 2022)
Abstract Objective This study aimed to examine the long-term effects of nonpharmacological interventions on reducing the diabetes incidence among patients with prediabetes and chronic complications events among patients with hyperglycemia (pre-diabetes and diabetes) by preforming a systematic review and meta-analysis of randomized controlled trials (RCTs). Methods PubMed, MEDLINE, EMBASE, the Cochrane Library and the Web of Science Core Collection were searched for studies published between January 1990 and November 2021, looking for RCTs to evaluate the effects of nonpharmacological interventions on preventing the incidence of diabetes and chronic complications in comparison with medical therapy, placebo, or usual diabetes care. Two independent reviews extracted relevant data and quality assessment. Any discrepancies were resolved by a third reviewer. Results In total, 21 articles involved 17 RCTs (follow-up ranged from 2 to 30 years) were included. Pooled analysis of intervention studies demonstrated clearly that nonpharmacological interventions have an significant effect on reducing the diabetes events in patients with prediabetes (RR 0.62; 95%Cl 0.54, 0.71). Pooled analysis of extended follow-up studies showed that nonpharmacological interventions could effectively reduce the diabetes incidence in patients with prediabetes (RR 0.78; 95%Cl　0.63, 0.96). Meta-regression and subgroup analysis indicates the diabetes incidence of long-term group (duration > 3 years) was clearly reduction by 0.05% compared with the relatively short-term group (duration ≤ 3 years). The incidence of microvascular complications in patients with hyperglycemia was effectively lowered by nonpharmacological interventions (RR 0.60; 95%Cl　0.43, 0.83). Conclusion Nonpharmacological interventions have a long-term effect on reducing the diabetes incidence among prediabetic patients, and effectively preventing microvascular complications on hyperglycemia.